Comparative evaluation of loop mediated isothermal amplification assay for rapid detection of Staphylococcus aureus - THAKUR, RASHMI; SINGH, RANDHIR; KAUR, SIMRANPREET; GILL, J P S (The Indian Journal of Animal Sciences, 2018)
A loop mediated isothermal amplification (LAMP) method for rapid detection of Staphylococcus aureus from milk using standard strain ATCC 33591 was optimized targeting thermonuclease (nuc) gene. LAMP protocol was optimized for detection of S. aureus at 62°C for 50 min in water bath. The analytical sensitivity of LAMP and qPCR was found to be equal, ca.102 CFU/ml, both in broth and spiked milk by commercial kit and phenol-chloroform-isoamyl method of DNA extraction, while the sensitivity of conventional PCR was low (ca. 103 and 104CFU/ml in broth and spiked milk samples, respectively), using kit method of DNA extraction. LAMP was 100% specific and in complete agreement with real time and conventional PCR. LAMP protocol optimized in the study was rapid and sensitive in detection of S. aureus in comparison to qPCR and PCR when kit method of DNA extraction was used. Application of LAMP for rapid detection of S. aureus on 126 field milk samples detected 93 milk samples positive out of 97 positive by culture without enrichment, hence giving sensitivity of 95.87%. Whereas, LAMP detected all 29 milk samples negative by culture as negative, thereby giving detection specificity of 100%. However, on enrichment of LAMP negative samples for four hours, LAMP could detect them positive for S. aureus. Enrichment of the milk sample for four hours enhanced the sensitivity of detection to 100% and detection limit to < 102 CFU/ml.